The Ukrainian Armed Forces educational and psychosocial junior officers’ professional competence development technology in the professional development system - VORONTSOV, Oleksandr (Journal of Education, Technology and Computer Science, 2013)
The article describes the necessary directions of the in-service training ofeducational and socio-psychological junior officers of the Ukrainian ArmedForces, the ways of construction of the training process of the in-service training.The educational and psychosocial junior officers professional competencedevelopment technology is envisaged in the in-service training